Black Panther : a nation under our feet. Book three - Coates, Ta-Nehisi; Lee, Stan, 1922-2018; Kirby, Jack (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2017)
The full truth of the People's revolution -- and the power players supporting it -- has been revealed! Now, T'Challa must fight like never before for the fate of his nation -- and one of his most trusted allies is back to stand by his side. As the final battle begins, the entirety of Wakanda's glorious history may be their most potent weapon. But even if the People fall, can the monarchy still stand?